The Gene Variants of Maternal/Fetal Renin-Angiotensin System in Preeclampsia: A Hybrid Case-Parent/Mother-Control Study - Zhang, Heng; Li, Ying-Xue; Peng, Wei-Jun; Li, Zhi-Wei; Zhang, Chun-Hua; Di, Hai-Hong; Shen, Xian-Ping; Zhu, Jun-Feng; Yan, Wei-Rong (Scientific reports, 2017)
Preeclampsia (PE) is a common pregnancy-related complication, and polymorphisms in angiotensinogen ( AGT ), angiotensin-converting enzyme ( ACE ), and angiotensin II type 1 receptor ( AT1R ) are believed to contribute to PE development. We implemented a hybrid study to investigate the influence of maternal and fetal ACE I/D, ACE G2350A, AGT M235T, AGT T174M, and AT1R A1166C polymorphisms on PE in Han Chinese women. Polymorphisms were genotyped in 1,488 subjects (256 patients experiencing PE, along with their fetuses and partners, and 360 normotensive controls with their fetuses). Transmission disequilibrium tests revealed that ACE I/D ( P = 0.041), ACE G2350A ( P = 0.035), and AT1R A1166C ( P = 0.018) were associated with maternal PE. The log-linear analyses revealed that mothers whose offspring carried the MM genotype of AGT M235T had a higher risk of PE (OR = 1.54, P = 0.010), whereas mothers whose offspring carried the II genotype of ACE I/D or the GG genotype of ACE G2350A had a reduced risk (OR = 0.58, P = 0.039; OR = 0.47, P = 0.045, respectively). Our findings demonstrate that fetal ACE I/D, ACE G2350A, AGT M235T, and AT1R A1166C polymorphisms may play significant roles in PE development among pregnant Han Chinese women.